Students’ Intention to Share Information Via Social Media: A Case Study of Covid-19 Pandemic - Hashim, Suhaizal; Masek, Alias; Abdullah, Nurhanim Saadah; Paimin, Aini Nazura; Muda, Wan Hanim Nadrah Wan (Universitas Pendidikan Indonesia, 2020)
Agility of science and technology in communication has brought a new dimension of information dissemination, which may have influenced human perceptions, especially on the dissemination of news pertaining to this pandemic. This research aims to determine the students’ sources of information regarding the COVID-19 disease and investigate their intention to share the information pertaining to COVID-19. A survey study was designed using an online questionnaire involving 147 higher education students. The online questionnaire; measures three elements of the students’ intention, namely initiative, desire and resourcefulness. The findings; the sources of information regarding the COVID-19 pandemic are mainly the government authorities and local healthcare workers. The most preferred medium of information regarding the COVID-19 pandemic is social media, and the most trusted medium is the television broadcast. Also, finding suggests that the students take initiative to verify information and demonstrate a desire to share credible and right information with their family and friends through social media. As such, in an effort or attempt to disseminate credible information about any important matters to the general public, the government can count on students as agents for transmitting the information to third parties including their family and friends.